2006
DOI: 10.1089/ten.2006.12.177
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Localization of Bone Growth Factors in Constructs of Biodegradable Scaffolds Seeded with Marrow Stromal Cells and Cultured in a Flow Perfusion Bioreactor

Abstract: Tissue engineering strategies aim at controlling the behavior of individual cells to stimulate tissue formation. This control is achieved by mimicking signals that manage natural tissue development or repair. Flow perfusion bioreactors that create culture environments with minimal diffusion constraints and provide cells with mechanical stimulation may closely resemble in vivo conditions for bone formation. Therefore, these culturing systems, in conjunction with an appropriate scaffold and cell type, may provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 30 publications
1
73
1
1
Order By: Relevance
“…Indeed, BMP-2, -4, and -7 are known to stimulate expression of bone ECM proteins BSP and OC, 47 while perfusion culture has been shown qualitatively to induce synthesis of growth and differentiation factors, including BMP-2 and TGF-b 1 . 12 However, this study-which may be the first to quantitatively characterize the induction of growth factors under flow-showed that different flow regimens resulted in different levels of expression of BMP-2, -7 (Fig. 5a), and TGF-b 1 (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, BMP-2, -4, and -7 are known to stimulate expression of bone ECM proteins BSP and OC, 47 while perfusion culture has been shown qualitatively to induce synthesis of growth and differentiation factors, including BMP-2 and TGF-b 1 . 12 However, this study-which may be the first to quantitatively characterize the induction of growth factors under flow-showed that different flow regimens resulted in different levels of expression of BMP-2, -7 (Fig. 5a), and TGF-b 1 (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Separately, perfusion culture of BMSCs has been shown to stimulate synthesis and accumulation of growth and differentiation factors, including bone morphogenetic protein (BMP)-2, fibroblast growth factor (FGF)-2, VEGF-A, and TGF-b 1 . 12 Together these data suggest that growth and differentiation factors-which accumulate in the ECM in response to hydrodynamic shear stress-may guide osteoblastic differentiation and contribute to enhanced expression of bone ECM proteins.…”
Section: Introductionmentioning
confidence: 89%
“…6,16,[23][24][25]30,34,48 However, static seeding is not an ideal method due to low efficiencies and poor cell distribution throughout the scaffold's porous network. 36,62,64 Consequently, it was important to evaluate the effects of flow perfusion in the seeding of polymeric scaffolds for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Natural-origin biomaterials have been considered for many years as a way to improve, in comparison to synthetic polymers, in vivo biofunctionality and to modulate/avoid a harmful host response due to their similarities with biological molecules. Starch-based scaffolds, processed using several methodologies aiming at a range of TE applications [19][20][21][22][23][24][25][26], have demonstrated great potential in this field. Very promising results for bone tissue regeneration have in particular been obtained with a blend of starch and polycaprolactone (SPCL) [20][21][22][23]25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Starch-based scaffolds, processed using several methodologies aiming at a range of TE applications [19][20][21][22][23][24][25][26], have demonstrated great potential in this field. Very promising results for bone tissue regeneration have in particular been obtained with a blend of starch and polycaprolactone (SPCL) [20][21][22][23]25,[27][28][29][30]. SPCL scaffolds, with adequate physicochemical and mechanical properties for bone TE [19,22] and adequate degradability rate [24,25,31], have been shown to support mesenchymal stem cell growth and differentiation [19,20], and to be excellent supporting structures for endothelial cells [22,23,32,33].…”
Section: Introductionmentioning
confidence: 99%